Pengaruh Model Pembelajaran Reading Identifying Constructing Solving Reviewing Extending (Ricosre) terhadap Kemampuan Literasi dan Keterampilan Proses Sains Peserta Didik Di Sekolah Menengah Atas Negeri 1 Tanjung Jabung Barat - Azzahra, Farida (Inspiratif Pendidikan, 2024)
Abstract: Literacy skills are the ability to apply concepts, scientific principles and understanding in everyday life. Integrating scientific literacy skills into learning is essential. Through thinking, understanding, and acting in scientifically accurate ways, literacy skills not only increase scientific knowledge but also improve process skills. Science process skills require students to analyze, create science, and gain knowledge through scientific procedures or methodology. The aim of this research is to determine the effect of the reading identifying constructing solving extending reviewing (RICOSRE) learning model on students' literacy abilities and science process skills in class XI human digestive system material at SMA Negeri 1 Tanjung Jabung Barat. This research uses a quantitative approach, with experimental methods. The design used was a pretest post-test control group design with a quasi-experimental research design pattern. The sample in this study amounted to 94 students. The instruments used were interviews, observation sheets, and test questions. The data analysis technique was carried out using Manova Analysis. Based on the results of statistical tests on the influence of the RICOSRE learning model on students' scientific literacy abilities, a value of 0.001<0.05 was obtained. Meanwhile, the sign value obtained for students' science process skills was 0.001<0.05. The conclusion was that the RICOSRE model had a significant influence on students' scientific literacy abilities and students' science process skills at SMA Negeri 1 Tanjung Jabung Barat. Keywords: RICOSRE, scientific literacy, science process, & students.